poetry style - pheuaphom, singthong (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The purpose of this study were to analyze models of versifications and to analyze phrases to use in poem for duration of 6 months, from Octrober in 2014 to Mach in 2015 that poets was published on internet with the total of 115 poems. The finding of this research were model of authorship that authors prefer using were poem “Sabphasod”, poem “Aksonesavad” and in order to others poem. In addition, the study of phraseology found that the favorite type of using in authorship were phraseology of rhetorical question and phraseology of simile. The way to write of poem has various models of versification, Othong Khaminsou is poet who does not repeat old model of versification, he improved model of versification that means the versification of poem is not followed by old model, the most vocabulary of usage are simple words, using any style of words, language is not hardened, nonviolent with imagine, every words used in poems with meaningful. The most phraseology is rhetorical phrases that prefer to ask without answering. In addition to use phraseology, the content of poem’s Othong Khaminsou focused to love as people who worship love more than all things that his poems occult with aspiration of love truly. Key words: POETRY STYLE, POETRY, PHRASEOLOGY.